Building Virtual Dominions - A Comparative Study of Mergers, Acquisitions and Strategic Alliances in E-commerce: Case Studies of Amazon.com and eBay. - Zilevicus, Stasys (2006)
This paper is aimed at finding motives and assessing consequences of mergers, acquisitions and strategic alliances of two world largest e-commerce companies' Amazon.com and eBay. It overviews a vast amount of theoretical literature on mergers, acquisitions and strategic alliances incentives and presents empirical literature findings on companies' financial and stock market's post-merger performance. Case studies section of the dissertation examines the history and motives of Amazon.com and eBay for engaging in mergers, acquisitions and strategic alliances activity, and measures the consequences of this activity by applying accounting and empirical financial approaches. Qualitative data is obtained from both online and published resources; the findings are that: 1. Mergers, acquisitions and strategic alliances contribute to increase in net sales revenues and cumulative customer base. 2. However, their impact on market share can be either positive or neutral. Quantitative data is taken from the companies' annual reports, business research companies' archives and financial website, Yahoo! Finance.com. The empirical models test four hypotheses, which concern the companies' financial and stock market performance. The findings of these models can be summarised as follows: 1. Mergers, acquisitions and strategic alliances can have either positive or negative effect on the companies' financial performances. 2. Mergers and acquisitions have either negative or close to zero effect on the companies' stock market's performance. 3. Strategic alliances have strongly positive effect on the companies' stock market's performance. 4. If strategic alliances are specified into marketing and technological alliances, the impact of both types on the companies' stock performance varies.